Palliation of dysphagia in metastatic oesogastric cancers: An international multidisciplinary position. (August 2020) - Levy, Antonin; Wagner, Anna D.; Chargari, Cyrus; Moehler, Markus; Verheij, Marcel; Durand-Labrunie, Jérôme; Kissel, Manon; Chirat, Erick; Burtin, Pascal; Ducreux, Michel; Boige, Valérie; Nilsson, Magnus; et al.
Abstract: Malignant dysphagia is the most common symptom in advanced oesogastric cancers patients. Relief of dysphagia allows quality of life improvement, nutritional replenishment and potentially improves prognosis. Chemotherapy alone is effective and should be prioritised in patients with metastatic disease a good performance status, and its impact on dysphagia should be determined before further interventions are planned. Regarding local treatments, the insertion of a covered self-expandable metallic stent is the most commonly used alternative, as it allows for the rapid relief of severe dysphagia. Although several randomised trials have highlighted the role of oesophageal brachytherapy, this technique is often not easily accessible. Contemporary trials are ongoing to better define the role of external radiation therapy. While awaiting these results, external radiation therapy can be considered as a second-best option for patients with a life-expectancy > 3 months. It is important to offer nutritional support and to integrate quality of life measures in the palliative management of dysphagia. This multidisciplinary international position paper aims to propose a decision-making process and highlight randomised trials for the management of malignant dysphagia in metastatic oesogastric cancer patients. Highlights: Chemotherapy is indicated in all patients with metastatic disease and a good PS. Oesophageal stent should be proposed, pending the implementation of another treatment or after its failure. Multidisciplinary approach, including nutritional support, a palliative care team and QoL/PROs are required. A decision-making diagram is proposed.